Femtosecond X-ray emission study of the spin cross-over dynamics in haem proteins - Dominik Kinschel (Nature Portfolio, 2020)
The change from low-spin hexacoordinated to high-spin pentacoordinated domed form in heam upon ligand detachment and the reverse process underlie the respiratory function. The authors, using femtosecond time-resolved X-ray emission spectroscopy, capture the transient states connecting the two forms in myoglobin-NO upon NO photoinduced detachment.